Sexual violence and associated factors among female night college students after joining the college in Debre Markos town, North West Ethiopia, 2019 - Wubedle Zelalem Temesgan; Zerfu Mulaw Endale; Getie Lake Aynalem (Elsevier, 2021)
Background: Violence against women is a significant public health problem as well as a fundamental violation of women's human rights. The magnitude of sexual violence in Africa is higher than in other regions and mostly occurs in school. However, data were limited on sexual violence against female night college students in Ethiopia at large. Method: Institutional based cross-sectional study was conducted among 422 participants in December 2019. Data were collected using pre-tested, self-administered questionnaire and simple random sampling technique. Each collected data were coded, cleaned and entered into EPI info version 7 and exported into SPSS version 20 for analysis. AOR with 95%CI and p-value of<0.05 were considered for the significant reports. Results: This research revealed that sexual violence in their lifetime, after joining the college and in the past 12 months were 27.1% (95%CI: 22.8, 31.1), 21.3% (95%CI: 17.4, 25.1) and 17.2% (95%CI: 13.8, 20.8) respectively. Residence being urban [AOR = 1.92 (95%CI: 1.03, 3.60)], more than 20 min taking to reach at the college [AOR = 1.82 (95% CI: 1.07, 3.07)], parents living condition separately [AOR = 1.89(95%CI: 1.08, 3.32)],Witnessed inter partner violence as a childhood [AOR = 2.55(95%CI:1.37,4.75)], alcohol intake sometimes [AOR = 3.24(95%CI:1.04,10.10)] and having multiple sexual partner [AOR: 6.42 (95CI: 2.27,18.16)] were positive predictors for sexual violence. Conclusion: The prevalence of sexual violence after joining the college among female night college students in Debre Markos town was high. Community awareness creation may be important to reduce the problem.